Photocatalytic degradation of paraquat over Cu-T1O2/SBA-15 - Sorolla, Maurice G. II (2011)
Photocatalytic degradation of paraquat using mesoporous-assembled Cu-TiO₂/SBA-15 under UV and visible light was investigated. The catalysts were synthesized by impregnation of Cu-TiO₂ colloids onto SBA-15. The colloids of Cu-TiO₂ were prepared via sol-gel method while the mesoporous support was prepared using hydrothermal technique. The catalysts were characterized using X-ray diffraction, nitrogen adsorption-desorption. UV-V is diffuse reflectance spectroscopy and Zeta potential. Results from characterization show that Cu doped TiO₂ has a small crystalline size and was well dispersed onto SBA-15. The inclusion of SBA-15 significantly enhanced the photocatalytic activity of the catalysts. Among the three types of undoped catalysts in this study (P25, TiO₂/SBA-15), TiO₂/SBA-15 yielded the highest degradation of paraquant for all pH under UV illumination. Meanwhile 2 wt% Cu-TiO₂/SBA-15 yielded the highest activity under visible light.